The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.4103/jfmpc.jfmpc_34_19
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the inhibitory characteristics of clinical instructors in the process of developing clinical competence of nursing students: a qualitative study

Abstract: Background: Different inhibitory factors may play a role in the process of developing the students’ clinical competence; among them, some of the characteristics of clinical instructors can be considered as the most important factors. Purpose: The aim of this study was to determine the inhibitory characteristics of instructors in the process of developing clinical competence in nursing students. Methods: This qualitative study was conducted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The findings obtained from the study demonstrated that Ineffective clinical instruction, Ineffective clinical administration, Ministerial challenges, and Student related challenges are the challenges in the clinical learning environment in the Nineveh governorate colleges of nursing. The first theme gathered in this study agreed with the previous study (Sadeghi et al, 2019),that point to subjectivism, a lack of scientific and nursing practice expertise, a lack of dedication to teaching, and a focus on routine learning were all evident indications of low clinical competence, which hampered students' ability to develop their clinical competence. The second theme of our study consistent with those (Achempim-Ansong et al, 2022), that mentioned, there are numerous challenges of clinical administration .…”
Section: Discussionsupporting
confidence: 86%
“…The findings obtained from the study demonstrated that Ineffective clinical instruction, Ineffective clinical administration, Ministerial challenges, and Student related challenges are the challenges in the clinical learning environment in the Nineveh governorate colleges of nursing. The first theme gathered in this study agreed with the previous study (Sadeghi et al, 2019),that point to subjectivism, a lack of scientific and nursing practice expertise, a lack of dedication to teaching, and a focus on routine learning were all evident indications of low clinical competence, which hampered students' ability to develop their clinical competence. The second theme of our study consistent with those (Achempim-Ansong et al, 2022), that mentioned, there are numerous challenges of clinical administration .…”
Section: Discussionsupporting
confidence: 86%
“…It encompasses the cognitive, psychomotor, and affective criteria, demonstrated by a set of educational objectives. This contributes to planning of the clinical simulation and development of instruments that aim to evaluate whether the participant, in this pedagogical strategy, developed clinical competence in nursing (33) .…”
Section: Debriefingmentioning
confidence: 99%
“…While student reports of ineffective clinical faculty are not exclusive to bridging students, 55,56 the uniqueness of PLPNs as learners with preexisting clinical knowledge and skills underscores a need to further explore the effectiveness of faculty in the clinical setting with a variety of student types. Bridging students in this review report being assigned to complete required clinical practicums on units where they already work as PLPNs 22,36 .…”
Section: Discussionmentioning
confidence: 99%